Some Theological Reflections on Religious Education - Smith, J. W. D. (Scottish journal of theology, 1953)
At the beginning of the twentieth century two theological influences could be traced in the provision made within the Protestant churches for the Christian nurture of youth.1 The first was the Calvinist emphasis on saving knowledge. For the Reformers themselves such saving knowledge was the fruit of faith. But the perils of controversy led later Protestant theologians to regard faith as orthodox doctrine about God rather than personal response to Him. This Calvinist emphasis on knowledge was reinforced by contemporary educational theory. The influence of Herbert was strong and intellectual instruction was regarded as the main concern of the day school. It was natural, therefore, that a sound factual knowledge of the Bible and of Christian doctrine should be accepted as the prime objective of Christian education.